A percepção da comunidade interna - um estudo de caso - Lima, Emanuel Edwan de (2001)
Communication has a vital role in our society today. We are living on the 'Information's Age' now, but sometimes the information itself does not convey into communication, which causes organizational problems and results on disturbed relationships within and among corporations. The objective of this work is to evaluate the perceptions of the production operators considering internaI communications practices in a company that operates on a serial production mode. In order to do that, an internaI communication framework is proposed, and from this framework we find the most important dimensions for the study of this communication. This research also covers a methodology for the development of a survey instrument intended to measure the leveI of perception of the internaI communication, as well as, develops a proposal methodology for analyses of its validation and reliability. The survey instrument is submitted on a sample of production operators of the Industrial Units of the studied company. A graphical analysis was executed from the collected data. After that, the most important points, those who required attention regarding the company's internai communication process, were observed, and actions were proposed for upgrading these processes.